2021
DOI: 10.1002/ece3.8006
|View full text |Cite
|
Sign up to set email alerts
|

What does it mean to be wild? Assessing human influence on the environments of nonhuman primate specimens in museum collections

Abstract: Objectives Natural history collections are often thought to represent environments in a pristine natural state—free from human intervention—the so‐called “wild.” In this study, we aim to assess the level of human influence represented by natural history collections of wild‐collected primates over 120 years at the Smithsonian Institution's National Museum of Natural History (NMNH). Materials and Methods Our sample consisted of 875 catarrhine primate specimens in NMNH collections, representing 13 genera collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…It is also possible that non‐captive baboons are still experiencing environments which are not entirely free from human influence, leading to anthropogenic changes in food availability. Eller et al ( 2021 ) analyzed 875 NHP specimens in the NMNH collections and found that over 90% of the NHP specimens do not come from so‐called “wild” settings as often assumed. Instead, these animals lived in habitats within terrestrial biomes of varying degrees of anthropogenic influence, designated and mapped as “anthromes” by Ellis et al ( 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also possible that non‐captive baboons are still experiencing environments which are not entirely free from human influence, leading to anthropogenic changes in food availability. Eller et al ( 2021 ) analyzed 875 NHP specimens in the NMNH collections and found that over 90% of the NHP specimens do not come from so‐called “wild” settings as often assumed. Instead, these animals lived in habitats within terrestrial biomes of varying degrees of anthropogenic influence, designated and mapped as “anthromes” by Ellis et al ( 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, these animals lived in habitats within terrestrial biomes of varying degrees of anthropogenic influence, designated and mapped as “anthromes” by Ellis et al ( 2010 ). The sample used by Eller et al ( 2021 ) included 41 of the 51 baboon specimens that are present in the current study. Of the 41 specimens with anthrome information, most (95.1%) lived and died in seminatural, rangeland, and cropland localities in southern and eastern Africa (Eller et al, 2021 ; Supplementary Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of great ape biological remains within natural history collections is largely the result of nineteenth to early 20th-century "Western" naturalists and animal dealers who traveled to the colonies of their empires, collecting dead specimens and live animals to bring back to museums, zoos, or for private sale. 37,38 As a result, great ape skeletal remains were a product of more than just the pursuit of scientific specimens as they were obtained under extractivist conditions and directly relate to colonial power and violence. 38 Extractivism is a colonial logic, practice, and mode of accumulation involving the removal of large quantities of natural resources from colonized regions for the benefit of the colonial powers.…”
Section: Colonial Historymentioning
confidence: 99%